2020
DOI: 10.1016/j.celrep.2020.02.053
|View full text |Cite
|
Sign up to set email alerts
|

The Dm-Myb Oncoprotein Contributes to Insulator Function and Stabilizes Repressive H3K27me3 PcG Domains

Abstract: Highlights d Myb transcriptional potentiation optimizes H3K4 methylation and RNA Pol II function d Myb contributes to insulator function and promotes binding of BEAF-32 and CP190 d Myb is required to stabilize H3K27me3 domains genome wide d Myb is enriched at TAD boundaries and chromatin loop anchors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…DroID co-regulation analysis of downregulated genes showed an abundance of highly significant insulator proteins including CTCF, CP190, BEAF-32, Chro, mod(mdg4), and the dREAM repressive complex subunits Myb, E2F2, lin-52, mip120 and mip130 (fig. 6F, right) (Bohla et al, 2014; Santana et al, 2020). The reason for this might be connected to the strong downregulation of ribosomal RNA and tRNA-producing genes observed in our functional analyses.…”
Section: Resultsmentioning
confidence: 99%
“…DroID co-regulation analysis of downregulated genes showed an abundance of highly significant insulator proteins including CTCF, CP190, BEAF-32, Chro, mod(mdg4), and the dREAM repressive complex subunits Myb, E2F2, lin-52, mip120 and mip130 (fig. 6F, right) (Bohla et al, 2014; Santana et al, 2020). The reason for this might be connected to the strong downregulation of ribosomal RNA and tRNA-producing genes observed in our functional analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we observed that CP190 still binds to most genomic sites associated with the Pita ΔCP1+2 protein in embryos. In many cases, these sites are associated with proteins that are known to be able to recruit CP190 [18,25,39,40,45,[65][66][67]. Such functional redundancy creates a stable and reliable architecture of regulatory elements, which is necessary for the correct regulation of genes during development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that CP190 still binds to most genomic sites associated with the Pita CP1+2 protein in embryos. In many cases, these sites are associated with proteins that are known to be able to recruit CP190 (25,(39)(40)(41)(62)(63)(64)(65). Such functional redundancy creates a stable and reliable architecture of regulatory elements, which is necessary for the correct regulation of genes during development.…”
Section: Discussionmentioning
confidence: 99%